Identification of Novel Biallelic TLE6 Variants in Female Infertility With Preimplantation Embryonic Lethality - Zhang, Manyu; Liu, Chunyu; Chen, Beili; Lv, Mingrong; Zou, Huijuan; Liu, Yajing; Gao, Yang; Wang, Tianjuan; Xing, Qiong; Zhu, Yutong; Wu, Huan; Zhang, Zhiguo; et al. (Frontiers in Genetics, 2021)
Preimplantation embryonic lethality is a rare cause of primary female infertility. It has been reported that variants in the transducin-like enhancer of split 6 (TLE6) gene can lead to preimplantation embryonic lethality. However, the incidence of TLE6 variants in patients with preimplantation embryonic lethality is not fully understood. In this study, we identified four patients carrying novel biallelic TLE6 variants in a cohort of 28 patients with preimplantation embryonic lethality by whole-exome sequencing and bioinformatics analyses, accounting for 14.29% (4/28) of the cohort. Immunofluorescence showed that the TLE6 levels in oocytes from patients were much lower than in normal control oocytes suggesting that the variants result in degradation of the TLE6 protein in oocytes. In addition, a retrospective analysis showed that the four patients underwent a total of nine failures of in vitro fertilization and intracytoplasmic sperm injection attempts and one of them became pregnant on the first attempt using donated oocytes. Our study extends the genetic spectrum of female infertility caused by variants in TLE6, further confirms previously reported findings that TLE6 plays a essential role in early embryonic development, and shows that patients harboring biallelic TLE6 variants are unlikely to get pregnant normally. In such case, oocyte donation may be the preferred treatment.